The association between china’s primary health care reform and inequalities in primary care utilisation and maternal mortality: a quasi-experimental longitudinal study from 2010 to 2019 - Chang Cai; Christopher Millett; Jin Xu; Yanshang Wang; Thomas Hone (International Journal for Equity in Health)
Abstract Background China’s maternal health has substantial inequalities across regions, a similar challenge faced by many low- and middle-income countries. The Chinese government launched a comprehensive health reform since 2015 to deliver more affordable and equitable primary health care (PHC), with pregnant women being a priority group of beneficiaries. However, little is known about the impacts of this PHC reform on primary care utilisation among pregnant women or maternal health inequalities. This study aims to examine whether and how China’s PHC reform affected primary care utilisation among pregnant women and maternity deaths differently across regions. Methods The study employed provincial-level panel data from the China Health Statistic Yearbook and China Statistic Yearbook (2010–2019). Reform implementation by province was identified using web-scrapping of 31 provincial government websites. Firstly, difference-in-differences method examined the reform impacts on visits to PHC facilities, the utilisation of family physician services and prenatal services, and the maternal mortality ratio (MMR). Secondly, fixed-effects panel regression models estimated the association between family physician service use, prenatal care and the MMR. Analyses were stratified by province human development index (HDI) to assess inequalities. Results The introduction of China’s PHC reform in a province was associated with increased utilisation of family physician services (59.7 per 10,000 people per year, 95% CI 32.8–86.5) and prenatal services (3.2% points per year, 95% CI 1.8–4.6) and reduced maternal death by 9.6 per 100,000 live births per year (95% CI 0.3–19.0) in low-HDI provinces. No reform impact was found in high-HDI provinces. In panel regression models for low-HDI provinces, with a 1.0% point increase in prenatal care utilisation and one increase in family physician visit per 100 people, maternal deaths would decrease by 1.4 (95% CI 0.2–2.5) and 2.4 (95% CI 1.4–3.5) per 100,000 live births per year, respectively. This association was not found in high-HDI provinces. Conclusion China’s PHC reforms and primary care utilisation were associated with reduction in MMR in less developed regions, suggesting contributions to lower inequalities in maternal health between regions. Community-level family physician services are likely effective for improving maternal health in high burden areas, but further system and quality improvements are needed in areas where maternal mortality is lower.